Determinants of Organizational Citizenship Behavior of Contract Employees - Surya, Ida Bagus Ketut; Kawiana, I Gede Putu; Riana, I Gede; Rihayana, I Gede (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 15 Nomor 1 Tahun 2021, 2021)
This study aims to analyze the effect of intrinsic motivation on job satisfaction and OCB and the effect of job satisfaction on OCB. This study also aims to analyze the indirect effect of intrinsic motivation on OCB  through job satisfaction. The study was conducted at the Secretariat of the Regional People’s Representative Council (DPRD) of Badung Regency. Data were collected by means of questionnaire using five scales, distributed to 143 contract employees. Before being fully disseminated, data quality testing was carried out using SPSS 20 to ensure the questionnaire was valid and reliable. The data collected were analyzed using descriptive and inferential analysis with WarpPLS. The results shows that intrinsic motivation plays an important role in increasing job satisfaction and OCB. Additionally, job satisfaction is also proven to be able to increase OCB. Furthermore, intrinsic motivation indirectly has an important role in increasing OCB  through job satisfaction.